(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article raises the issue of inclusive teaching system in a preschool education. In the course of inclusive education, there is an increase in pedagogical skills, an increase in the pedagogical competence and responsibility of teachers and parents, the educational space of the preschool educational institution is expanding and its social status is increasing.